National medical service
1943-10-20 1943 1940s 15 pages -12- In any good National Medical Service the General Medical Practitioners, in the vanguard of medical practice, seeing patients at their homes or in their surgeries meeting disease in its earliest stages and in its most chronic or terminal phases, should be afforded every facility not only for treatment to patients but for diagnosis and investigation, for specialist consultant opinion and for following up his case or cases to the end, in hospital or convalescence or return to work. Consultants and Specialists - Instead of only being available in institutions, or at a fee in domiciliary practice beyond the reach of the ordinary worker, specialists in every sphere should be available in mobile teams, or in Health Centres as appropriate to every case needing such services. Laboratory services and specialists should also be available in any organsed [organised] medical service, local or national. At present many local authorities provide such services for cases of tuberculosis, V.D., Maternity centres, and for institutions dealing with infections, and other diseases. When patients are admitted to hospitals, such services may be available but in many cases, even in difficult cases or in the early stages of obscure or unusual ailments the ordinary patient has great difficulty even with his doctor in attendance in obtaining readily such faciliti [facilities] Ancillary Services - These include Health Visiting, Nursing, Physiotherapy (Massage, Ray treatment etc.) as well as Dispensing, Welfare Officers, Almoners etc. All these services, well organised and perfectly co-ordinated should be readily and immediately available at any stage of illness as required. General Principles of a National Health Service. 1. These have been briefly summarised in a previous document. They may be very briefly set out again as follows :- (a) The National Health Service, with a firm emphasis on Optimum Civil Health for each and every citizen, and the Prevention of Disease as its main aim, should be administered and co-ordinated centrally through a Government Department - the Ministry of Health - responsible to Parliament. (b) The Service must be provided without cost and on equal terms to all citizens without any distinctions, and the very best medical advice and treatment appropriate to the disabling condition must be uniformly availalbe [available]. (c) The institutional Medical Services, Hospitals, clinics, convalescent homes, rehabilitation centres, must all be unified and administered as a single health accessory service, with provision for delegation of powers to regional, and further to local, representative bodies. (d) The ancillary services - X-ray and Pathological workers, Midwives, nurses, Welfare workers, health visitors, laboratory assistants, ambulance workers etc. - must also be regarded as an important section included in the unified services. (e) The education and training of the medical and ancillary personnel employed in the National Health Service must be one of the primary duties of the National Health Administration, not only with regard to undergraduate or prediplomate education but also to postgraduate facilities, specialist training, medical 292/847/2/113